Online news portals in Malaysia: revisit of the regulatory regime governing the media in the era of media convergence - Nawang, Nazli Ismail; Mohamed, Abdul Majid Tahir; Mustaffa, Aminuddin (UUM Press, 2020)
Online news portals such as Malaysiakini, Malaysia Today and many others have been instrumental in providing alternative news and information to the Malaysian public. These portals are currently treated differently from print media as they need not procure a licence or permit before publishing online content. Conversely, print media proprietors are mandated by the Printing Presses and Publications Act 1984 to hold valid printing licences and publication permits before offering their services. Further, the presence of the no censorship guarantee of the Internet appears to render online news portals and other online publications to be free from legislative control. This is undesirable as there appears to be two different sets of regulatory frameworks for traditional media and new media. Hence, this paper will trace the historical development of online news portals in Malaysia, analyse the existing regulatory regime which govern print media and new media, and examine the potential application of these laws to regulate online news portals. By adopting a qualitative approach, the study employed a combination of doctrinal and comparative analysis. A doctrinal analysis was adapted to explore the current regulatory framework in order to address the legal predicament faced by online news portals. Further, the study applied a comparative analysis method by examining current practices and experience in the United Kingdom (UK). For this reason, the study scrutinised relevant statutory provisions and other secondary sources comprising textbooks, academic journals, seminar papers, and other pertinent materials found in newspapers and/or reputable websites. In conclusion, it is submitted that the same set of laws and regulations should be applied to govern print media and online news portals here, similar to the practice adopted by the Independent Press Standards Organisation (IPSO) in the UK.